The sustainable development : an islamic perspective / Mohammed Amer Younus, Azila Ahmad Sarkawi and Ako Mustafa Rasool - Younus, Mohammed Amer; Sarkawi, Azila Ahmad; Rasool, Ako Mustafa (2012)
In 1987, the United <ations released the Brundtland Report, which included what is now one of the most widely recognized definition of sustainable development is “development that meets the needs of the present without compromising the ability of future generations to meet their own needs." It contains within it two key concepts, i) The concept of 'needs', in particular the essential needs of the world's poor, to which overriding priority should be given; and ii) The idea of limitations imposed by the state of technology and social organization on the environment's ability to meet present and future needs."((WCED), 1987). All definitions of sustainable development require that people see the world as a system—a system that connects space; and a system that connects time. When people think of the world as a system over space, they grow to understand that air pollution from <orth America affects air quality in Asia, and that pesticides sprayed in Argentina could harm fish stocks off the coast of Australia.(IISD, 2011). The concept of sustainable development is rooted in sort of systems thinking. It helps people understand themselves and the world. The problems that world facing are complex and serious. Therefore, the concept of sustainable development is not a development of one of its element. The U< took the initiative of raising the slogan of ‘Development without Environmental Destruction’ and in requesting all governments to take positive steps towards rationalizing the use of natural resources. The term of ‘Sustainable Development’ which emerged in the 1970s (after the U< Conference) to express the interdependence between development and environment has been given many definitions and explanations. In fact, the debate around the new term has produced a kind of ‘conceptional confusion’.The concept of sustainable development has triggered debate on the issue of justice in the distribution of natural resources among successive generations. Justice in the distribution of natural resources within the context of successive generations means that those who live now on this planet should not be extravagant in the consumption of resources or misuse them, since this will create problems for those who are to come after them(Yousri).As has been elaborated above, sustainable development, which is attached with a number of principles highlighting its nature and goals.